Mouse models to investigate cell cycle and cancer - Kaldis, Philipp (Henry Stewart Talks, 2009)
Cell cycle regulation during mouse development and adulthood, Cyclin-dependent kinases (Cdks), The genetic pathways for cell cycle regulation, Cdk1, Cdk2, Cdk4, and Cdk6, The in vivo functions of Cdk2, Compensation between different Cdk/cyclin complexes, Genetic interaction between Cdk2 and Cdk4, Control of the G1/S phase transition by the Retinoblastoma protein (Rb), DNA damage response in the absence of Cdk2, p27Kip1 inhibits Cdk1 in vivo, Cdk1/cyclin E complexes promote S phase, Cdks and tumors
Updated at 2020/05/28